Pengaruh Tingkat Kesadaran Masyarakat Dalam Pembayaran Pajak Terhadap Kepatuhan Wajib Pajak (Studi Kasus Kantor SAMSAT Kisaran) - Supardi; Siti Aisyah (Institut Teknologi dan Sains Mandala, 2023)
Tax is an important contribution that must be paid to the government which is coercive in nature, which is then used as a state expense. Taxes are also a source of financing to improve and equalize the welfare of the community. This study aims to determine the effect of the level of public awareness in paying taxes on taxpayer compliance. The research method used by the researcher is a qualitative descriptive method by conducting observations and interviews to collect data. Data obtained from several journals, books and internet sources related to the title of the discussion in the preparation of this journal. The location of the research was carried out at the Kisaran SAMSAT Office.